Household Air Pollution in Low- and Middle-Income Countries: Health Risks and Research Priorities - Martin, William J. (Public Library of Science, 2013)
William Martin and colleagues report on their stakeholder meetings that reviewed the health risks of household air pollution and cookstoves, and identified research priorities in seven key areas. Please see later in the article for the Editors' Summary